Tense in Mandarin Chinese Sentences. (14th July 2015) - Lin, Tzong‐Hong Jonah
Abstract J. Lin (2010) argues against Sybesma's (2007) proposal that Mandarin Chinese has syntactic tense and contends that it does not need tense for the temporal interpretations of sentences. This paper shows that those arguments cannot be sustained. Specifically, this paper points out the following: (i) Lin's claim that Mandarin Chinese sentences do not show tense‐related syntactic properties is wrong. (ii) The so‐called nonexistent temporal interpretations of Mandarin Chinese sentences are merely a matter of choice of the reference time. (iii) Lin's argument against the existence of past tense in Mandarin Chinese is committed to the error of taking the English past tense as the only model for the tense system of Mandarin Chinese. (iv) The parallelism between Dutch and Mandarin Chinese that Sybesma observes is temporal in nature, despite the objections of Lin. (v) The temporal interpretations of Mandarin Chinese sentences can be accounted for straightforwardly by a pronominal tense system.